A Clinical Comparative Study on the Efficacy of Nirgundi Patra Pinda Sweda with and without Matra Basti in the Management of Janu Sandhigat Vata w.s.r. to Osteoarthritis of Knee - Nakum, Alpa R; Sharma, Akanksha; Ruparel, Sweety; Shukla, Ram (International Research Journal of Ayurveda & Yoga, 2022)
In Vridhdhavastha, Vata Dosha is in a dominant state and Rasadi Dhatus are in a deprived state. This potent combination is responsible for the aged being vulnerable to many diseases. Among them, Sandhigata Vata, which is equated to Osteoarthritis, stands top in the list of geriatric diseases. In current study efforts have been made to evaluate & compare the effect of Nirgundi Patra Pinda Sweda with and without Matra Basti on Janu Sandhigata Vata. Aims and objectives: To evaluate & compare the effect of Nirgundi Patra Pinda sweda with and without Matra Basti in the management of Janu Sandhigat Vata w.s.r to Osteo-arthritis. Materials and Methods: 30 Patients of Janu Sandhigata Vata were selected according to the classical signs and symptoms of Sandhigata Vata according to Ayurveda as well as Modern science, were randomly divided into 2 groups from the Govt. Akhandanand Ayurved Hospital, Ahmedabad. In group A 15 patients were treated with Nirgundi Patra Pinda Sweda And Matra Basti with Ashwagandhadi Taila and in group B 15 patients were treated with only Nirgundi Patra Pinda Sweda. Result 20.00% patients got marked improvement and 80.00% got moderate improvement in group A and in group B 33.33% patients got moderate improvement and 66.67% showed mild improvement. Nirgundi Patra Pinda Sweda and Matra Basti with Ashwagandhadi Tail provided better result as compare to only Nirgundi Patra Pinda Sweda on management of Janu Sandhigata Vata.